(untitled) (INNOVATIVE ECONOMY, 2020)
Fedulova L.I. TRENDS OF INNOVATIVE UKRAINE’S ECONOMY DEVELOPMENT AS THE RESULTS OF THE STATE POLICY Purpose. Determination of innovation development trends in Ukraine, substantiation of problems and influences factors, as well as development of recommendations regarding directions of increasing the efficiency of innovation policy in the implementation of the concept of neoindustrialization. Methodology of research included the application of the provisions of the theory and practice of innovation and the principles of the economic-technological paradigm as the methodological basis of the analytical assessments carried out; methods of statistical analysis, analogy and structuring of goals, generalization for revealing characteristic processes and development of proposals for improvement of innovation policy as an integral part of the state strategy of socio-economic development. Findings. The dynamics and trends of the development of science, scientific and technological activity and innovation activity of enterprises in Ukraine are determined on the basis of official statistics data. According to the results of the international ratings, Ukraine’s position on "technological readiness" and "innovation" components has been analyzed and it has been established that during the years 2013-2018 they had some positive dynamics. The problems of innovation of the country’s economy and factors influencing the nature of the implementation of innovative processes in recent years, among which the activation of the defense industry sector of the country’s industry has been noted. It is substantiated that the challenges to the global trend of socialization of technologies in Ukraine are not answered, and the extremely negative factor in the country should be acknowledged by the low level of the ability of authorities of all levels to maintain and attract the intellectual resource of the nation, in comparison with the leaders of the countries of innovation. Recommendations were developed regarding the directions of increasing the efficiency of innovation policy in implementing the concept of neoindustrialization. Originality. The scientific novelty of the research is to identify and justify the trends of innovative development of the Ukrainian economy and to deepen the scientific-theoretical and practical provisions for the formation of a new innovation policy taking into account the possibilities of its introduction in the conditions of implementation of neoindustrialization. Practical value. The use of the developed provisions will allow the bodies of management of socio-economic processes of different levels to more clearly take into account valuation indices and ratings in the formation of an appropriate innovation policy as an integral part of strategic innovation development, identify the directions and mechanisms for strengthening international scientific and technological cooperation, develop and implement innovative programs within the framework of the European Integration of the Ukrainian economy. Key words: trends; innovation; innovation policy; neoindustrialization; innovative development.